The pressure to go above and beyond the call of duty: Understanding the phenomenon of citizenship pressure among teachers. (July 2019) - Somech, Anit; Bogler, Ronit
Abstract: This study investigated the phenomenon of citizenship pressure (CP) - a job demand in which employees feel pressured to engage in citizenship behavior - among teachers, by exploring its nature, sources, and consequences. Results of in-depth semi-structured interviews provide initial support for the validity of the concept in the school context. Interviewees referred to both external and internal pressures, with the former seemingly more prevalent. Results indicate that CP impacts individuals as well as the school as a whole. Findings suggest that principals should encourage teachers to exhibit citizenship behaviors voluntarily, without paying the costs of acting under undesirable pressure. Highlights: Teachers experience continuous pressure to perform OCB. Management was the most salient force that exerts pressure to engage in OCB. Citizenship pressure impacts the individual and the school as a whole.